Reno(r/m)mer « la » lesbienne ou quand les lesbiennes étaient féministes - Diane Lamoureux (Genre, Sexualité et Société)
This article analyzes three major contributions to US feminist analysis of lesbianism in the 1970s, those of radicalesbians, Anne Koedt and Adrienne Rich. All three aim to naming and defining this “unidentified political object”, “the” (in the singular) lesbian. I will begin with a detailed analysis of those contributions. On this basis, I will then identify their theoretical foundations and the problems that they raise regarding critical lesbian viewpoints.